Activation of Methane and Carbon Dioxide Mediated by Transition‐Metal Doped Magnesium Oxide Clusters [MMgO]+/0/− (M=Sc–Zn). Issue 21 (13th April 2015) - Li, Jilai; González‐Navarrete, Patricio; Schlangen, Maria; Schwarz, Helmut
<x xml:space="preserve">Abstract</x> Mission: impossible? DFT calculations show that the trends in the thermochemistry are very different for the activation of CO2 and CH4 mediated by transition‐metal doped magnesium oxide clusters [MMgO]+/0/− (M=Sc–Zn). Thus, seeking a "simple" reagent to simultaneously mediate activation and coupling of CH4 and CO2 with high efficiency seems extremely daunting, if not impossible.